Design of Dual-Axis Sunflower Type Solar Tracker to Improve Solar Panel Efficiency - Iti, Mohammad Rifki; Asmara, Bambang Panji; Abdussamad, Syahrir; Musa, Wahab; Bonok, Zainudin; Nadifa, Ulfatun (Jambura Journal of Electrical and Electronics Engineering, 2025)
This study aims to design and test a sunflower-type solar tracker system based on light sensors to improve energy conversion efficiency in solar panels. This system uses four LDR sensors and two servo motors controlled by a microcontroller to automatically direct the panel following the movement of the sun throughout the day. The research method used is an engineering experiment, which includes literature studies, design, implementation, and system testing in sunny and cloudy weather conditions. The test results show that in sunny conditions, the tracker system produces 15.60 Wh of energy, while the static panel is only 5.81 Wh. In cloudy conditions, the energy produced by the tracker system decreases to 0.68 Wh (a decrease of 95.61%), while the static panel only produces 0.047 Wh (a decrease of 99.19%). Overall, the tracker system shows an increase in efficiency of 34.25% compared to the static system. These findings indicate that the Sunflower Solar Tracking system is effective in increasing the efficiency of solar energy absorption, even in less than optimal lighting conditions.Penelitian ini bertujuan untuk merancang dan menguji sistem pelacak surya tipe sunflower berbasis sensor cahaya guna meningkatkan efisiensi konversi energi pada panel surya. Sistem ini menggunakan empat sensor LDR dan dua motor servo yang dikendalikan oleh mikrokontroler untuk mengarahkan panel secara otomatis mengikuti pergerakan matahari sepanjang hari. Metode penelitian yang digunakan adalah eksperimen rekayasa, yang mencakup studi literatur, perancangan, implementasi, serta pengujian sistem pada kondisi cuaca cerah dan mendung. Hasil pengujian menunjukkan bahwa pada kondisi cerah, sistem pelacak menghasilkan energi sebesar 15,60 Wh, sedangkan panel statis hanya 5,81 Wh. Pada kondisi mendung, energi yang dihasilkan oleh sistem pelacak menurun menjadi 0,68 Wh (penurunan 95,61%), sementara panel statis hanya menghasilkan 0,047 Wh (penurunan 99,19%). Secara keseluruhan, sistem pelacak menunjukkan peningkatan efisiensi sebesar 34,25% dibandingkan sistem statis. Temuan ini mengindikasikan bahwa sistem Sunflower Solar Tracking efektif dalam meningkatkan efisiensi penyerapan energi surya, bahkan pada kondisi pencahayaan yang kurang optimal.